Efficacy of reuterin and bacteriocins nisin and pediocin in the preservation of raw milk from dairy farms - Kumar, Nirmal; Kumar, Vinay; Waheed, Syed Mohsin; Pradhan, Diwas (2021)
Research background. In the current scenario of milk production in developing and developed countries, several factors influence the shelf-life of raw milk and add significant numbers of microbial contaminants that drastically lower the initial microbial quality leading to milk spoilage by the time it reaches the processing units. Experimental approach. The present study was undertaken to investigate the biopreservative efficacy of reuterin system along with different combinations of bacteriocins in controlling the initial microflora of raw milk at farm level. Lactobacillus reuteri strain LR47, having effective antimicrobial activity, was shortlisted from our previous study and further characterized for reuterin production and tested in raw milk system. Results and conclusions. Preliminary testing of the cell-free supernatant from L. reuteri LR47 demonstrated significant growth inhibition of the majority of the tested bacterial indicators of milk spoilage. Further genetic analysis of the L. reuteri LR47 revealed the presence of two genes (pduC and dhaB) involved in the utilization of glycerol to produce reuterin via two different pathways. The strain LR47 was also found to possess comparatively higher capacity to convert glycerol into reuterin when checked through colourimetric assay. In the raw milk biopreservation experiment with reuterin alone or in combination with bacteriocins, the highest level of growth suppression in the total bacterial load and coliform counts was observed in the sample that was treated with a combination of reuterin, nisin and pediocin. The treatment combining these three natural biopreservatives at specific concentrations was able to maintain the initial microbial quality and extend the shelf-life of raw milk by 6 h at 37 °C based on the microbial counts and physicochemical properties, viz. pH and titratable acidity.
Pozadina istraživanja. Pri današnjoj proizvodnji mlijeka u razvijenim zemljama te onima u razvoju, nekoliko čimbenika utječe na trajnost sirovog mlijeka i pojačava kontaminaciju patogenim mikroorganizmima, što bitno utječe na inicijalnu populaciju mikroorganizama i uzrokuje kvarenje mlijeka prije početka obrade. Eksperimentalni pristup. U ovom je radu ispitana učinkovitost reuterina kao biokonzervansa u različitim kombinacijama s bakteriocinima za kontrolu mikroflore sirovog mlijeka na farmi. U našem je prethodnom radu zbog izražene antimikrobne aktivnosti od nekoliko sojeva bakterija odabran soj Lactobacillus reuteri LR47, te je ispitana njegova sposobnost proizvodnje reuterina u sirovom mlijeku. Rezultati i zaključci. Preliminarni su testovi pokazali da je supernatant bez stanica bakterije L. reuteri LR47 bitno inhibirao rast većine ispitanih uzročnika kvarenja mlijeka. Daljnje genetičke analize soja otkrile su prisutnost dvaju gena (pduC i dhaB) odgovornih za iskorištenje glicerola tijekom dva različita metabolička puta proizvodnje reuterina. Osim toga, kolorimetrijskom je analizom otkriveno da soj LR47 ima veću sposobnost konverzije glicerola u reuterin od ostalih sojeva bakterija. Pri ispitivanju postupaka biološkog konzerviranja sirovog mlijeka pomoću reuterina ili reuterina u kombinaciji s bakteriocinima, najizraženije je svojstvo inhibicije ukupnog broja mikroorganizama i broja koliformnih bakterija zapaženo u uzorku mlijeka tretiranog kombinacijom reuterina, nizina i pediocina. Broj mikroorganizama i fizikalno-kemijska svojstva, kao što su pH-vrijednost i titracijska kiselost, pokazali su da se kombinacijom određenih koncentracija tih triju prirodnih biokonzervansa očuvala početna mikrobiološka kakvoća mlijeka, te produljila njegova trajnost za 6 sati pri 37 °C.
Bibliografija: 48 jed.
Summary ; Sažetak.
Keywords: Mlijeko -- Konzerviranje mlijeka -- Reuterin -- Bakteriocini -- Lactobacillus reuteri